Raspberry Pi Projects for Kids. - Bates, Daniel (Computer science researcher) (Community experience distilled., 2014)
This tutorial contains all-important information about how to use your Raspberry Pi to develop any application you like. It is broken down into several action-packed projects, each containing easy-to-follow steps, just to show you how easy and fun computer programming can be!If you are someone with a big imagination and would like to dive straight into the realm of technology and computers, then this is the book for you. With only a Raspberry Pi and no prior experience required, you will be shown how to translate your ideas into computer programs, creating any game, tool, or animation you can.